Pleistocene glacial geomorphology and chronology of the Nahuel Huapi-Limay and Traful catchments, northern Patagonia - Mizerit, Ignacio; Morabito, Ezequiel Garcia; Bechis, Florencia; Terrizzano, Carla M.; Groos, Alexander R.; Rugel, Georg; Merchel, Silke; Zech, Roland (Geomorphology, 2025)
The Nahuel Huapi Lake-Limay River catchment and the Traful River catchment are key localities for reconstruction of Quaternary glaciations and environmental changes in northern Patagonia. These sites present very well preserved glacial landforms; their location with respect to the Andes mountains allows us to evaluate the influence of the Southern Westerly Winds on the past climate at 41°S. In an attempt to refine the local timing of past glaciations in this region, we present mapping results and fourteen in situ 10Be exposure ages from boulders of different moraine systems that reflect a series of pronounced past glacial advances. We combine our age constraints with recalculated previously published moraine boulder ages. The surface exposure ages suggest that the Nahuel Huapi/Limay outlet glacier reached positions close to its maximum extent of the last glacial cycle at 112.3 ± 2.4 ka. This age implies glacier expansion during a colder period at the beginning of the Last Glacial period (Marine Isotope Stage 5d), out of phase with global ice volume records, although an older age for this advance cannot be ruled out. We suggest that the northward migration of the Southern Westerly Winds, coupled with an increase in precipitation, could be contributing factors to this glacial advance. During the Last Glacial Maximum, a less-extensive advance occurred at 26.8 ± 1.4 ka in the Nahuel Huapi-Limay River catchment and between 26.8 ± 5.4 and 24.1 ± 4.3 ka in Traful River catchment.
CRIS-Team Scopus Importer:2025-06-13
Keywords: Cosmogenic nuclide surface exposure dating; Glacial chronology; Glacial geomorphology; Northern patagonian ice sheet evolution; Quaternary landscape evolution; Quaternary paleoclimate